Association of Acupuncture and Auricular Acupressure With the Improvement of Sleep Disturbances in Cancer Survivors: A Systematic Review and Meta-Analysis - Wan, Qingyun; Luo, Shuting; Wang, Xiaoqiu; Tian, Qianmo; Xi, Hanqing; Zheng, Shiyu; Fang, Qinqin; Chen, Hao; Wu, Wenzhong; Pan, Rui (Frontiers in Oncology, 2022)
Background: Researches into acupuncture and auricular acupressure on sleep disturbances in cancer patients have been growing, but there was no specific and comprehensive systematic review and meta-analysis. This review aims to evaluate the efficacy and safety of acupuncture and auricular acupressure on sleep disturbances in cancer survivors based on existing randomized clinical trials (RCTs). Methods: Four English-language and four Chinese-language biomedical databases were searched for RCTs published from database inception to July 30th, 2021. RCTs compared acupuncture and auricular acupressure with sham control, drug therapy, behavior therapy, or usual care for managing cancer were included. The quality of RCTs was appraised with the Cochrane Collaboration risk of bias (ROB) tool. Mean differences (MD) and 95% confidence intervals (CI) were calculated for the effect sizes. Results: Thirteen RCTs with 961 patients were included. The risk of performance bias or reporting bias for most included trials were high or unclear. Evidence was not found for short-term effects on sleep scales compared to sham control (MD, 1.98; 95% CI, 0.33 to 3.64; P = 0.02; I2 = 36%), wait list control (MD, 0.40; 95% CI, -0.87 to 1.68; P = 0.54; I2 = 49%), drug therapy (MD, 1.18; 95% CI, -3.09 to 5.46; P = 0.59; I2 = 98%). For long-term effect, two sham-controlled RCTs showed no significance of acupuncture on insomnia scale scores (MD, 1.71; 95% CI, -2.38 to 5.81; P = 0.41; I2 = 89%). Subgroup analyses suggested no evidence that auricular acupressure (MD, 3.14; 95% CI=1.52, 4.76; P = 0.0001; I2 = 0%) or acupuncture (MD, 0.54; 95% CI=-1.27, 2.34; P = 0.56; I2 = 0%) was associated with the reduction of insomnia scale scores. Conclusions: This systematic review and meta-analysis found no evidence about acupuncture or auricular acupressure in the improvement of sleep disturbances in cancer survivors in terms of short-term or long-term effect. Adverse events were minor. The finding was inconsistent with previous research and suggested more well-designed and large-scale randomized controlled trials were needed to identify the efficacy of acupuncture and auricular acupressure for sleep disturbances in cancer survivors. Trial Registration: CRD42020171612.